Русская культура: монография / Д. С. Лихачев - Лихачев Дмитрий Сергеевич (Искусство, 2000)
Экземпляры: ЦБ (2001) / Инвентарный номер: 34420 / Цена: 356.06 / Сис.шифр: 71.0 / Авт.знак: Л 65 / ГРНТИ: 13 / ББК: 71.0